2018
DOI: 10.1111/eve.12984
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophils of the horse: Part I: Development, distribution, structure and biochemical mediators

Abstract: Summary Eosinophils are becoming the target of increasing research interest as recent studies suggest that their role in immune homoeostasis and the immune response to disease is far more complex than previously understood. Historically, the horse eosinophil has been used to study basic eosinophil biology because of the considerable volume of blood required to obtain enough viable cells for reliable, repeatable experiments. This resulted in a large but disseminated body of literature pertaining to the structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 96 publications
(113 reference statements)
0
7
0
Order By: Relevance
“…Moreover, different subpopulations of eosinophils have been identified, which could be related to as many different functions; for example, in human medicine, it has been observed that the eosinophilic population residing in the lungs shows several differences compared with the eosinophilic population recruited from the airways (Brosnahan, 2018). Furthermore, some eosinophils at steady state demonstrated to have a function in homeostasis regulation (homeostatic eosinophils, hEOS): these eosinophils are different from the inflammatory eosinophils (iEOS) recruited in case of infection or allergic disease (Weller & Spencer, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, different subpopulations of eosinophils have been identified, which could be related to as many different functions; for example, in human medicine, it has been observed that the eosinophilic population residing in the lungs shows several differences compared with the eosinophilic population recruited from the airways (Brosnahan, 2018). Furthermore, some eosinophils at steady state demonstrated to have a function in homeostasis regulation (homeostatic eosinophils, hEOS): these eosinophils are different from the inflammatory eosinophils (iEOS) recruited in case of infection or allergic disease (Weller & Spencer, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Eosinophils are involved in homeostatic pathways in other species (Marichal et al ), but these have not been investigated in the horse. The objectives of Eosinophils of the horse: Part II are to review existing observations on eosinophils in clinical diseases, to interpret in the context of Part I (Brosnahan ) and research in other species, and to identify the salient research questions that will further our understanding of the eosinophil in equine health and disease.…”
Section: Introductionmentioning
confidence: 99%
“…I agree with the authors that these variable observations in peripheral blood eosinophilia may be attributed to differences in the timing of blood collection. In addition, as I discussed in ‘Eosinophils of the horse: Part I: Development, distribution, structure and biochemical mediators’ (Brosnahan, 2020b), peripheral blood eosinophil counts also have been documented to vary by time of day, sex of horse (Gill & Rastawicka, 1986; Kottman‐Jutter, 1975) and season (Gill et al., 1985) in healthy horses. Noting time of day of blood collection in addition to experimental timing, and making every effort to keep this consistent across experiments, may help to reduce the chance of confounding variation in eosinophil counts in future reports by all of us who study eosinophils.…”
mentioning
confidence: 99%
“…
Thank you for providing the opportunity to respond to comments from Drs. Birkmann and Fettelschoss-Gabriel submitted in reference to 'Eosinophils of the horse: Part II: Eosinophils in clinical diseases' (Brosnahan, 2020a(Brosnahan, , 2020b.The authors begin by noting that the pathogenesis of insect bite hypersensitivity (IBH) in horses may also involve a type IVb hypersensitivity reaction. They further present newer data from their research group that demonstrated a clear increase in both localised and peripheral blood eosinophils, and a correlation of peripheral blood eosinophils with severity of disease.
…”
mentioning
confidence: 99%
See 1 more Smart Citation